(untitled) - Silverstein, Shel (New York, 2011)
The second original book to be published since Silverstein's passing in 1999, this poetry collection includes more than one hundred and thirty never-before-seen poems and drawings completed by the cherished American artist and selected by his family from his archives.
Keywords: Poetry,Thơ